Point Spread Function For Elliptical Aperture Inclined at ^/4 angle with x-axis - Y. Hasan, Sundus; H. Tarkhan, Widad (JOURNAL OF ADVANCES IN PHYSICS, 2014)
Point spread function (PSF) for inclined elliptical aperture with an angle equal to p/4 with x-axis has been studied, by taking new coordinates m and n which are rotated by an angle p/4 to x and y- axes. The properties of the obtained image have been found in different cases, for diffraction limited system and different types of aberrations, like focus error, spherical aberration and coma aberration.